2011
DOI: 10.2147/jpr.s24393
|View full text |Cite
|
Sign up to set email alerts
|

fMRI in patients with lumbar disc disease: a paradigm to study patients over time

Abstract: Low back pain is a common human ailment. It is estimated that over 70% of the population will experience low back pain that will require medication and/or medical attention. There are many causes for low back pain, one being herniation of the discs of the lumbar spine. Treatment options are very limited. Why patients develop chronic pain especially when there is no known organic cause or when the offending painful stimulus has been removed remains poorly understood. Functional magnetic resonance imaging (fMRI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…В настоящее время имеются сведения о том, что вследствие активизации процессов воспаления грыжи межпозвонковых дисков могут подвергаться инволюции [10]. В ряде случаев грыжа межпозвонкового диска несет в себе опасность нарушения функций невральных структур, однако нередко даже значительных размеров грыжа, выявленная при радиологическом обследовании, не является основной причиной ПБ [11]. Далеко не всегда наблюдается соответствие между размерами и локализацией грыжи межпозвонкового диска и наличием и характером ПБ.…”
Section: основные причины возникновения пбunclassified
“…В настоящее время имеются сведения о том, что вследствие активизации процессов воспаления грыжи межпозвонковых дисков могут подвергаться инволюции [10]. В ряде случаев грыжа межпозвонкового диска несет в себе опасность нарушения функций невральных структур, однако нередко даже значительных размеров грыжа, выявленная при радиологическом обследовании, не является основной причиной ПБ [11]. Далеко не всегда наблюдается соответствие между размерами и локализацией грыжи межпозвонкового диска и наличием и характером ПБ.…”
Section: основные причины возникновения пбunclassified
“…For example, a study by Giesecke et al (2004) demonstrated that patients with cLBP had more extensive neuronal activation in pain-related brain cortical areas than healthy controls in response to the application of pressure with a thumbnail. Another study by Sharma et al (2011) used a straight leg raise maneuver to stimulate pain during fMRI and detected increased brain activity within the anterior cingulate gyrus, bilateral insular regions, right thalamus, basal ganglia, and sensorimotor regions. In addition, published literature has also provided evidence for increased brain activation in several brain regions after the application of mechanical stimuli to the low back area (Kobayashi et al, 2009;Manchikanti et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Although there have been many attempts to devise experimental pain models of LBP, which applied mechanical [8,9], thermal [7,10], chemical [11] stimulations on the back or limbs, these methods hardly induce pain akin to the endogenous back pain [12,13]. Nevertheless, the straight leg raise (SLR) maneuver has been considered as a sensitive test to diagnose lumbar disc herniation (sensitivity = 0.91) [14,15], and previous neuroimaging researches have reported that the SLR maneuver activates brain regions of the pain processing by exacerbating LBP [7,16,17,18].…”
Section: Introductionmentioning
confidence: 99%